2007
DOI: 10.1111/j.1447-073x.2007.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Supratrochlear foramen of the humerus

Abstract: The presence of the supratrochlear foramen was studied in 150 dry adult humeri, of unknown sex from the Department of Anatomy, St John's Medical College, Bangalore: The dimensions of the foramen were measured. In bones where the foramen was absent, opacity or translucency of the septum was observed. A supratrochlear foramen was found in 28% of the total humerii. It was almost equal in number on both the sides (right, 27.9%; left, 27.8%). Most of the foramina were oval in shape, their transverse and vertical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 6 publications
8
49
1
1
Order By: Relevance
“…Diwan et al [9] have shown similar frequencies of septal aperture in both sexes. There are studies where the dominance of the right humerus in septal aperture frequency has been observed [28,39]; and there are also studies where the similar incidence of septal aperture on both sides has been observed [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diwan et al [9] have shown similar frequencies of septal aperture in both sexes. There are studies where the dominance of the right humerus in septal aperture frequency has been observed [28,39]; and there are also studies where the similar incidence of septal aperture on both sides has been observed [39].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with this trait may be able to overextend the elbow joint [8]. The frequency of the foramen among mankind ranges from about 0.3% to 60%, in different races [for the details see 18,28,34,35,39]. The cause of septal aperture has been widely discussed; however, the problem has not been solved yet.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that the bones obtained from our department belonged to individuals from Jining; Jining is a small city with a majority of local residents. The Japanese population in the Kyusu district had a prevalence of 18.1% (16,17), with a higher frequency of 20.6% in females and a lower frequency of 13.5% in males. Among Indians, a prevalence of 32% was found in Central India, whereas a lower prevalence was reported among South (28%), North (27.5%), and East Indian (27.4%) population groups, as reviewed by Singhal and Rao (17).…”
Section: Prevalence Of Stf In Other Populations and Comparison With Tmentioning
confidence: 99%
“…Because mechanical loads on epiphyses experienced before adulthood may produce changes in these structures (Blackburm, 2011), they are therefore manifest in the complete humerus. These differences could be reflected in features such as humeral torsion (Rhodes, 2006;Rhodes and Churchill, 2009;Roach et al, 2012), septal perforation in the olecranon fossa (Singhal and Rao, 2007), and the carrying angle (Paraskevas et al, 2004;Tükenmez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have observed that the larger size of the olecranon fossa and lesser breadth of the distodorsal pillars in Neanderthals compared with H. sapiens is a classical feature of this human group (Vandermeersch and Trinkaus, 1995;Bacon, 2000;Rosas et al, 2015). There are several studies about septal perforation in the modern human population (Singhal and Rao, 2007;Ndou et al, 2013) that suggest that the larger size and septal perforation are the result of bone resorption caused by an intermittent pressure of ulna olecranon or coronoid processes on the septum of the humerus during the flexion-extension movement of the elbow, which produces a greater hyperextension of this joint. In Neanderthals, this same phenomenon could explain the larger size of the left olecranon fossa.…”
Section: Discussionmentioning
confidence: 99%